How Strongly the Body Mass Index (BMI) Is Associated with Inter Arm Blood Pressure Difference: BMI association with IAD - Alam, Muhammad Absar; Rehman, Anam; Manzoor, Javaria; Zafar, Zafar Ali; Jawed, Shireen; Altaf, Benash (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To explore the association between the body mass index (BMI) and inter arm difference (IAD) blood pressure and to understand how these factors influence blood pressure. Study Design: Cross-sectional study. Place and Duration of Study: Aziz Fatimah Medical and Dental College Faisalabad Pakistan, from Nov to Dec 2020. Methodology: Total 100 healthy medical students aged 19-21 years were included in the study. Height in meters and weight in kilograms were documented by stadiometer (ZT-100). BMI was assessed by Quetelet’s index (BMI=weight in Kg/height in m2). Blood pressure was recorded simultaneously in both arms by the auscultatory method. Inter arm difference in blood pressure was estimated by calculating differences in diastolic and systolic pressures between the right and left arm. Results: Mean age of the participants was 19.83 ± 1.23 years. Significant difference was noted in systolic and diastolic interarm blood pressure among obese and non-obese groups (p-values <0.001). BMI was positively associated with diastolic and systolic inter-arm blood pressure (p-values <0.001). Conclusion: Body mass index is positively associated with inter arm difference in blood pressure, and both positively impact the blood pressure.